The Role of Father Involvement and Marital Satisfaction in the Development of Family Interactive Abilities: A Multilevel Approach - Simonelli, Alessandra; Parolin, Micol; Sacchi, Chiara; De Palo, Francesca; Vieno, Alessio (Frontiers in Psychology, 2016)
The present study aims to investigate, using multilevel analysis, the development of family interactions from pregnancy to preschool age, in a longitudinal perspective. Moreover, it intends to explore the impact of couple relationship and father involvement in childcare on the developmental trend of the quality of mother-father-child interactions. 103 primiparous families were assessed at 7th month of pregnancy, 4th, 9th, 18th months of child’s life and during preschool age (36-48th), using the observational procedure named Lausanne Trilogue Play. Parents’ perception of marital satisfaction was assessed with the Dyadic Adjustment Scale at each point of measure; moreover, in the postnatal assessment parents completed the Father Involvement Questionnaire. Results showed that family interactions increase over time. Second, a decrease of marital adjustment is associated to an improvement of the quality of family interactions. Moreover, father involvement predicts the quality of family interactions from the earliest stages of child’s life. In a longitudinal perspective, family interactions and marital quality show opposite developmental trends and father’s involvement represents a particularly important feature of the family.